Signaling Status with Luxury Goods: The Role of Brand Prominence - Han, Young Jee; Nunes, Joseph C.; Drèze, Xavier (Journal of Marketing, 2010)
This research introduces “brand prominence,” a construct reflecting the conspicuousness of a brand's mark or logo on a product. The authors propose a taxonomy that assigns consumers to one of four groups according to their wealth and need for status, and they demonstrate how each group's preference for conspicuously or inconspicuously branded luxury goods corresponds predictably with their desire to associate or dissociate with members of their own and other groups. Wealthy consumers low in need for status want to associate with their own kind and pay a premium for quiet goods only they can recognize. Wealthy consumers high in need for status use loud luxury goods to signal to the less affluent that they are not one of them. Those who are high in need for status but cannot afford true luxury use loud counterfeits to emulate those they recognize to be wealthy. Field experiments along with analysis of market data (including counterfeits) support the proposed model of status signaling using brand prominence.